Phytochemical profile, antioxidant activity, and sun protection potential of selected Annonaceae species - Djamil, Ratna; Clarissa Iskandar, Maria; Kartika Pratami, Diah (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Excessive sun exposure can damage the skin, highlighting the need for effective natural sunscreens. This study aimed to evaluate the phytochemical profile, antioxidant activity, total phenolic content (TPC), total flavonoid content (TFC), and sun protection factor (SPF) of five Annonaceae species. Methanolic leaf extracts of Annona muricata (soursop), Annona squamosa (sugar apple), Cananga odorata (cananga), Annona reticulata (nona), and Monoon longifolium (glodokan tiang) were analyzed. Phytochemical screening was performed to identify secondary metabolites. Antioxidant activity was determined using the DPPH radical scavenging assay, while TPC and TFC were measured spectrophotometrically. SPF values were calculated using the Mansur method. Phytochemical screening confirmed the presence of flavonoids, saponins, tannins, steroids, and phenolics in all extracts, with cananga leaves additionally containing alkaloids, coumarins, and essential oils. The DPPH assay showed antioxidant activity with IC₅₀ values ranging from 12.89–228.98 ppm, classified from very strong to weak. TPC and TFC values ranged from 12.33–31.75 mg GAE/g extract and 8.83–28.19 mg QE/g extract, respectively. SPF values ranged from 19.32–35.03, indicating all extracts fall under the ultra-protection category, with soursop leaf extract exhibiting the highest SPF. This study highlights the potential of Annonaceae leaf extracts, particularly A. muricata, as promising natural antioxidant and photoprotective agents due to their high polyphenolic and flavonoid content.